Unveiling the Distinctive Impact of Vocational Schools Link and Match Collaboration with Industries for Holistic Workforce Readiness - Yoto; Suyetno Agus; Wibawa Aji Prasetya; Paryono; Romadin Achmad (Open Education Studies)
This study examines vocational schools (VS) collaborative ventures, focusing on the VS Center of Excellence and its partnerships with local industries. The research explores how these collaborations shape a skilled workforce by investigating the Link and Match policy’s impact. Specifically studying machining engineering and construction in East Java, the research employs a multi-case qualitative approach to reveal context-specific insights. The study combines qualitative methods like interviews and observations with quantitative techniques such as surveys using a mixed-method approach. The sample comprises internship supervisors from significant industries in East Java, selected through proportionate random sampling. Thematic analysis is used for qualitative data, while descriptive statistics and Likert scale analysis handle quantitative data. The research offers insights into workforce needs by emphasizing technical competencies and soft skills development. It also looks ahead, considering the long-term effects of collaborative initiatives on graduates and industries. The study informs policymakers and educators by identifying challenges and aiming to enhance vocational education strategies. However, it is essential to recognize data collection biases and limitations in generalizability to other locations or sectors, which should be considered when interpreting findings and planning future research.